2008
DOI: 10.1002/er.1443
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the enthalpy of PCM as a function of temperature using a heat-flux DSC-A study of different measurement procedures and their accuracy

Abstract: SUMMARYThermal energy storage by latent heat allows storing high amounts of energy working in narrow margins of temperature. The use of phase change material (PCM) for the latent heat storage has been studied in different applications and it has been commercialized in containers to transport blood, products sensible to temperature, to decrease their energy demand. The use of PCM in cooling and refrigeration has been attracting a lot of interest lately, but for all applications, the properties of these material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(73 citation statements)
references
References 8 publications
(8 reference statements)
3
70
0
Order By: Relevance
“…This phenomenon in PCMs is referred to as 'hysterisis' and it is particularly significant with certain types of PCM, for example inorganic PCMs. However, past research [Castellon, 2008] has shown that, at very slow heating and cooling rates (~0.1C/min), the hysteresis effect in paraffinic PCMs, such as the present nano-PCM, is negligible. In fact, the DSC data shown in Figure 1 and Figure 2 show that the phase change temperatures during cooling and heating are nearly identical.…”
Section: Materials Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…This phenomenon in PCMs is referred to as 'hysterisis' and it is particularly significant with certain types of PCM, for example inorganic PCMs. However, past research [Castellon, 2008] has shown that, at very slow heating and cooling rates (~0.1C/min), the hysteresis effect in paraffinic PCMs, such as the present nano-PCM, is negligible. In fact, the DSC data shown in Figure 1 and Figure 2 show that the phase change temperatures during cooling and heating are nearly identical.…”
Section: Materials Propertiesmentioning
confidence: 66%
“…Annual simulations were done using typical meteorological year (TMY3) 4 weather data for Charleston. EnergyPlus 5 was used to create input files of hourly solar radiation and exterior heat transfer coefficients for the different wall orientations.…”
Section: Annual Simulation In Charleston Using Tmy3 Datamentioning
confidence: 99%
“…The few milligrams of mortars samples necessary for DSC testing were gathered by drilling of the hardened mortar. Methodology and rationale Generally, the standard measurement method for the analysis of many thermo-physical properties is the DSC [17]. A literature survey [17][18][19] revealed that there are different possibilities of operation methods to analyse PCM through DSC tests.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Methodology and rationale Generally, the standard measurement method for the analysis of many thermo-physical properties is the DSC [17]. A literature survey [17][18][19] revealed that there are different possibilities of operation methods to analyse PCM through DSC tests. The two most common methods are: the dynamic method, which corresponds to a constant heating rate and the step method, which consists in applying variable heating rates to the sample [18].…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“….1 This calibration shall be performed once for each apparatus, using the test procedure based on Tleoubaev et al (9). A1.2 The correction factor is not equal to the specific heat of the transducers themselves because the temperature profile through the transducer thickness is not linear until the temperature within the apparatus plate has reached steady state.…”
Section: Annexes (Mandatory Information)mentioning
confidence: 99%